Effect of sucralose on the enzyme kinetics of invertase using real-time NMR spectroscopy and progress curve analysis. (2nd January 2018) - Her, Cheenou; Singh, Jaideep; Krishnan, V.V.
Abstract: Sucralose, a derivative of sucrose, is widely used in noncaloric artificial sweeteners (NAS). Contrary to the belief that sucralose is physiologically inert and a healthy alternative sweetener to natural sugar, emerging studies indicate that sucralose alters the host metabolism as well as the composition of the microbiome. In this manuscript, we use real-time nuclear magnetic resonance (NMR) spectroscopy to demonstrate that sucralose alters the enzymatic conversion of sucrose to glucose and fructose. The real-time NMR progress curve analysis suggests that sucralose has the characteristic of a competitive inhibitor on the kinetics of the enzymatic process. This affects the rate of glucose production, and thus indirectly affecting the mutarotation process of α-D-glucose to β-D-glucose conversion. At a 1:2 M ratio of sucrose to sucralose, the results show that the catalytic efficiency of the enzyme is reduced by more than 50% in comparison to the measurements without sucralose. Altogether, as sucralose alters the rate of glucose production, sucralose cannot be considered inert to the metabolism as several downstream events in both prokaryotic and eukaryotic systems strongly depend on the rate of glucose metabolism. Graphical abstract: Highlights: Real-time NMR experiment to measure enzyme kinetics with progress curve analysis. Role of artificial sweetener sucralose on the enzyme kinetics of invertase. Sucralose alters the enzyme kinetics of sucrose as a competitive inhibitor.